Impedimetric Enzyme‐Free Detection of Glucose via a Computation‐Designed Molecularly Imprinted Electrochemical Sensor Fabricated on Porous Ni Foam. Issue 5 (27th January 2017) - Li, X.; Niu, X.H.; Wu, H.Y.; Meng, S.C.; Zhang, W.C.; Pan, J.M.; Qiu, F.X.
Abstract: Here we report a new molecularly imprinted electrochemical sensor (MIECS) for the impedimetric enzyme‐free analysis of glucose. A computational modeling strategy was first utilized to screen promising functional monomers for imprinting assembly, and simulation data suggested that methacrylic acid (MAA) exhibited a preferable capability to recognize the target molecule compared to other common monomers. Then the MIECS was prepared via introducing MAA‐based recognition sites onto a porous Ni foam with large surface. The fabricated sensor was subtly characterized by Raman spectroscopy, scanning electron microscopy, and cyclic voltammetry, and an impedimetric method was selected to detect the glucose target in a basic medium. Experimental results demonstrated that the proposed MIECS could selectively recognize glucose against coexisting species, with good linear responses of the charge transfer resistance upon the target concentration in the scope of 10∼55 mM. These results indicate its potential applications in the recognization and detection of glucose in complex matrices. Abstract :